2017
DOI: 10.1002/jmri.25605
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute thermal damage volumes in muscle using magnetization‐prepared 3D T2‐weighted imaging following MRI‐guided high‐intensity focused ultrasound therapy

Abstract: Purpose To evaluate magnetization-prepared 3D T2-weighted MR imaging measurements of acute tissue changes produced during ablative MR-HIFU exposures. Methods A clinical MR-HIFU system (3T) was used to generate thermal lesions (n=24) in the skeletal muscles of three pigs. T1-weighted, 2D T2-weighted, and magnetization-prepared 3D T2-weighted sequences were acquired before and after therapy to evaluate tissue changes following ablation. Tissues were harvested shortly after imaging, fixed in formalin, and gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 41 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, there was good agreement in Bland–Altman plots. Staruch et al reported similar correlations for lesion size in pig muscle measured between T 2 W and contrast‐enhanced T 1 W images, following MRI‐guided high‐intensity focused ultrasound therapy …”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Furthermore, there was good agreement in Bland–Altman plots. Staruch et al reported similar correlations for lesion size in pig muscle measured between T 2 W and contrast‐enhanced T 1 W images, following MRI‐guided high‐intensity focused ultrasound therapy …”
Section: Discussionmentioning
confidence: 75%
“…In our study, the laser beam activation time at each location varied from 60 sec to 120 sec. This could produce variations in the tissue damage . These variations were not considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations